Formación del sujeto político estudiantil: percepción y desarrollo en estudiantes de grado noveno y undécimo del Instituto Susana Wesley (2021)
This research monograph seeks to identify what perceptions regarding the construction of political culture and its development have the ninth and eleventh grade students of the Susana Wesley Institute, a private formal education institution located south of Bogotá.